Terrorismo extremo e os tensionamentos nas democracias - Hugo Arend (Ciências Sociais Unisinos)
This article interprets how democratic institutions are tensioned in a unique way by extreme terrorism. What are the peculiarities of this new extreme terrorism and how are they related to the construction of big cities? How can we relate the conflicts that emerge in the midst of big cities after terrorist attacks and the problems faced by Western democracies? The article proposes an alternative way of conceiving of the conflicts that emerge from terrorist attacks in a globalized world, a way that challenges the theory of the clash of civilizations.